2023
DOI: 10.3847/1538-4357/ad0839
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Horizontal and Vertical Oscillation of a Quiescent Filament Observed by CHASE and SDO

Jun Dai,
Qingmin Zhang,
Ye Qiu
et al.

Abstract: In this paper, we present the imaging and spectroscopic observations of the simultaneous horizontal and vertical large-amplitude oscillation of a quiescent filament triggered by an extreme-ultraviolet (EUV) wave on 2022 October 2. Particularly, the filament oscillation involved winking phenomenon in Hα images and horizontal motions in EUV images. Originally, a filament and its overlying loops across AR 13110 and 13113 erupted with a highly inclined direction, resulting in an X1.0 flare and a non-radial coronal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 104 publications
3
1
0
Order By: Relevance
“…Notably, these computed magnetic field strength values should have significant uncertainties, which should be smaller than the actual value because the speeds utilized here are smaller than the actual speeds since the projection effect. Similar to the reports by Shen et al (2014aShen et al ( , 2014b, Dai et al (2023) reported a Moreton wave confirmed by CHASE, where the accompanying EUV wave triggered a simultaneous horizontal and vertical oscillation of a quiescent filament. Unfortunately, we carefully checked the data from CHASE and other devices and found that the Moreton wave did not accompany the present event.…”
Section: Discussionsupporting
confidence: 87%
“…Notably, these computed magnetic field strength values should have significant uncertainties, which should be smaller than the actual value because the speeds utilized here are smaller than the actual speeds since the projection effect. Similar to the reports by Shen et al (2014aShen et al ( , 2014b, Dai et al (2023) reported a Moreton wave confirmed by CHASE, where the accompanying EUV wave triggered a simultaneous horizontal and vertical oscillation of a quiescent filament. Unfortunately, we carefully checked the data from CHASE and other devices and found that the Moreton wave did not accompany the present event.…”
Section: Discussionsupporting
confidence: 87%
“…where B r , ρ p , and r 0 represent the radial component of the magnetic field, density, and scale height of the prominence, 1), respectively, and assuming ρ p = 4 × 10 −14 g cm −3 , we can estimate B r to be 5.4 G. Likewise, the radial magnetic field of the filament can also be calculated, yielding an estimate of 4.1 G. This is close to the values reported in previous papers (Hyder 1966;Shen et al 2014aShen et al , 2017Zhang & Ji 2018;Dai et al 2023).…”
Section: The Oscillation Of the Prominence And Filamentsupporting
confidence: 87%
“…As shown in Figure 9, the prominence exhibits simultaneous horizontal and vertical oscillations, indicative of transverse oscillations. This implies that the normal vector of the wave is inclined downward toward the prominence (Takahashi et al 2015;Dai et al 2023;Zheng et al 2023), which appears to provide strong support for the discussion of the properties of the EUV wave above (see also Figure 9 in Shen et al 2014b).…”
Section: The Oscillation Of the Prominence And Filamentsupporting
confidence: 54%
“…This could be caused by two reasons. (i) Due to the oscillation, a quiescent filament moved downward and thus showed a redshifted absorption around 20:25 UT (Dai et al 2023). This could influence the full-disk Sun-as-a-star profiles of the flare.…”
Section: Influence Of the Size Of The Tr On The Sun-as-a-star Spectrummentioning
confidence: 99%